2016
DOI: 10.7120/09627286.25.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A tool for the evaluation of slaughter horse welfare during unloading

Abstract: This study aimed to develop a scientific and practical tool to be used to assess horse welfare after commercial transport over long journeys. A set of physical, behavioural and environmental measures was selected, covering welfare aspects of both transport and unloading procedures. The protocol was field-tested on 51 intra-EU commercial transports arriving at different sites in Italy. Univariate analysis was implemented to look for associations between the input variables (environmental hazards potentially aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 37 publications
1
31
2
Order By: Relevance
“…The number of animals to be assessed was estimated assuming an expected proportion of welfare issues of 14%, with 5% absolute precision and 99.5% confidence interval (CI). The expected proportion of welfare issues was obtained by averaging the proportions of severe injuries and animals with poor welfare found by Marlin et al [ 1 , 9 , 11 ] (i.e., 23%, 18.6%, and 0.1%, respectively). The minimum sample size required was 365 horses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of animals to be assessed was estimated assuming an expected proportion of welfare issues of 14%, with 5% absolute precision and 99.5% confidence interval (CI). The expected proportion of welfare issues was obtained by averaging the proportions of severe injuries and animals with poor welfare found by Marlin et al [ 1 , 9 , 11 ] (i.e., 23%, 18.6%, and 0.1%, respectively). The minimum sample size required was 365 horses.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence of the effects of transportation to slaughter is scant [ 8 ]. While dead animals on arrival (DOA) or in the lairage were never recorded, the prevalence of severe welfare issues varied from study to study [ 1 , 9 , 10 , 11 ]. Marlin et al [ 1 ] found that 23% out of 1519 horses unloaded in Italy after long journeys (arriving from Poland and Romania) had at least one acute injury and 10% were severely lame.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a body of literature reporting about the effect of training to load in sport horses [i.e., (4, 11, 14, 16)], nothing has been published on meat horses completely naïve to transport. This study population deserves great attention because horses kept for meat production are generally transported to the slaughterhouse without any training [see (2022) for a review], with adverse effects on their welfare (7, 23, 24). It was consequently hypothesized that self-loading training would reduce the time to load, stress-related behavior, and behavioral problems during loading in meat horses.…”
Section: Introductionmentioning
confidence: 99%